Cuba's new social structure: Assessing the re-stratification of Cuban society 60 years after revolution - Katrin Hansing; Bert Hoffmann (German Institute of Global and Area Studies (GIGA), 2019)
Few political transformations have attacked social inequalities more thoroughly than the 1959 Cuban Revolution. However, as the survey data in this paper shows, 60 years on, structural inequalities which echo the pre-revolutionary socio-ethnic hierarchies are returning. While official Cuban statistics are mute about social differences along racial lines, the authors were able to conduct a unique, nationwide survey which shows the contrary. If the revolutionary, state-run economy and radical social policies were the main social elevators for the formerly underprivileged classes in socialist Cuba, the economic crisis and depressed wages of the past decades have seriously undercut these achievements. Moreover, previously racialised migration patterns have produced highly unequal levels of access to family remittances, and the gradual opening of the private business sector in Cuba has largely disfavoured Afro-Cubans, due to their lack of access to pre-revolutionary property and remittances in the form of start-up capital. While social and racial inequalities have not yet reached the levels of other Latin American countries, behind the face of socialist continuity a profound restructuring of Cuban society is taking place.
Keywords: 300; Cuba; social inequality; race; socialism; migration; remittances